2015
DOI: 10.1080/15459624.2015.1018518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultraviolet Germicidal Irradiation (UVGI) on N95 Respirator Filtration Performance and Structural Integrity

Abstract: The ability to disinfect and reuse disposable N95 filtering facepiece respirators (FFRs) may be needed during a pandemic of an infectious respiratory disease such as influenza. Ultraviolet germicidal irradiation (UVGI) is one possible method for respirator disinfection. However, UV radiation degrades polymers, which presents the possibility that UVGI exposure could degrade the ability of a disposable respirator to protect the worker. To study this, we exposed both sides of material coupons and respirator strap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
374
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(388 citation statements)
references
References 13 publications
6
374
0
5
Order By: Relevance
“…Their lowest applied dose of 120,000 mJ/cm 2 reduced the bursting strength of the four N95 models tested by 11% to 42% (depending on the model and the individual layer), with very minor effects on filter aerosol penetration and filter airflow resistance (Table 3). An applied dose of 590,000 mJ/cm 2 reduced the breaking strength of straps from the four N95 FFR models tested by 10% to 21% 36 . It should be noted that their lowest dose is 120,000 mJ/cm 2 , which is 60 times higher than the conservative minimum dose of 2,000 mJ/cm 2 we recommend for SARS-CoV-2 inactivation.…”
Section: Uvgimentioning
confidence: 97%
See 1 more Smart Citation
“…Their lowest applied dose of 120,000 mJ/cm 2 reduced the bursting strength of the four N95 models tested by 11% to 42% (depending on the model and the individual layer), with very minor effects on filter aerosol penetration and filter airflow resistance (Table 3). An applied dose of 590,000 mJ/cm 2 reduced the breaking strength of straps from the four N95 FFR models tested by 10% to 21% 36 . It should be noted that their lowest dose is 120,000 mJ/cm 2 , which is 60 times higher than the conservative minimum dose of 2,000 mJ/cm 2 we recommend for SARS-CoV-2 inactivation.…”
Section: Uvgimentioning
confidence: 97%
“…Strap strength was unaffected by 10 UVGI cycles (total applied dose 10,000 mJ/cm 2 ), but 20 cycles had some effect on certain models. • Lindsley et al 36 went further, estimating the cumulative effect of extremely high exposures of N95 FFRs to UVC in order to mimic repeated cycles of UVGI treatment. Their lowest applied dose of 120,000 mJ/cm 2 reduced the bursting strength of the four N95 models tested by 11% to 42% (depending on the model and the individual layer), with very minor effects on filter aerosol penetration and filter airflow resistance (Table 3).…”
Section: Uvgimentioning
confidence: 99%
“…Another disadvantage is that UVGI was reported to significantly impact the mechanical strength of some FFRs with doses of around 1000 J/cm 2 . 34 Therefore, UVGI may be a useful disinfection technique, but the exact exposure or intensity of the UV-C light fluence on the mask surface would need to be verified. The variation in UVGI intensity has been the cause of discrepancies in the literature, as 3M's own internal reports recently showed that their UVGI treatments damaged particular FFRs, 35 whereas other reports show that UVGI cycling on multiple N95 FFRs had minimal or no impact.…”
mentioning
confidence: 99%
“…The only study to observe either type of damage used a range of very high doses of UVGI. 4 At their lowest dose (120 Jcm −2 ), the only significant damage was that, for one model of mask, one layer of the filter became significantly more susceptible to being punctured by a steel ball (decreased burst strength). At higher doses damage gradually became more significant.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, multiple studies have addressed this question. 4,5,12,13 Their results are summarized in table 1.…”
Section: Introductionmentioning
confidence: 99%